Hearing preservation of post-radiotherapy for acoustic neuroma—a systematic review and meta-analysis - Musleh, Abdullah; Alshehri, Sarah (Frontiers in Neurology, 2025)
ObjectiveAcoustic neuroma (AN), or vestibular schwannoma, is a benign tumor of the eighth cranial nerve. Radiotherapy is a key treatment modality. This systematic review and meta-analysis evaluate post-radiotherapy hearing preservation in patients with AN.MethodsFollowing PRISMA guidelines, 36 studies published from 2011 to 2020 were identified through searches in PubMed, Cochrane, and Semantic Scholar. Data from 3,903 patients were analyzed using RevMan 5.3. Random-effects models were applied to account for heterogeneity.ResultsThe pooled hearing preservation rate post-radiotherapy was 55.9%. Gamma Knife and single-session protocols were associated with higher preservation rates. Male sex was linked to a significantly higher risk of hearing loss (RR = 0.83, 95% CI: 0.69–0.99). Tumor control was achieved in the majority of cases (RR = 2.95, 95% CI: 1.94–4.29). Hearing preservation declined with longer follow-up durations. Secondary outcomes included tinnitus, imbalance, and facial nerve dysfunction.ConclusionRadiotherapy offers favorable tumor control with variable hearing preservation, influenced by treatment modality, sex, and follow-up duration. These findings inform patient counseling and support the need for standardized outcome measures in future studies.